KADAR KOLESTEROL PADA BEBERAPA BAGIAN TUBUH AYAM POTONG JANTAN YANG DIBERI FORMULA PAKAN DENGAN DEDAK PADI KONSENTRASI TINGGI - -, Siswanto (Buletin Veteriner Udayana, 2012)
An experiment was carried out to study thecholesterol concentration on some parts of thebody ofthe broilers cockerels that given hight ricebran supplement in the feedon cholesterolconcentration of the meed, liver, serum, skin, and abdomen fat at Physiology laboratory,Udayana University, Denpasar City. The aims of the experiment was to study cholesterolconcentration on some parts of the body ofthe broilers cockerels.Thirty broiler cockerelsDOC CP707 wererandomizedand divided into three treatments consisted of40%ricebran(P1); 60% ricebran (P2); and without ricebran as controle (P0). The treatment was startedat 3 weeks of age and terminated when the cockerels aged 7 weeks. Results of this experimentshowed that there weresignificant differences decrease (P? 0,05) ofricebran supplement onthe meet cholesterol and skin cholesterol, but significant differences increase (P ? 0,05)onthe liver cholesterol. And no significant differences (P ± 0,05)on fat abdoment.Theconclution that dietary ricebran influence the cholesterol concentration of the some parts ofthe body in broilers cockerels
Keywords: ricebrand, cholesterol, broilers cockerels